Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Bahan Bakar Kendaraan Bermotor (PBBKB) dan Dampaknya terhadap Belanja Daerah di Provinsi Kalimantan Timur - Indriyanti, Ana; Roy, Juliansyah; Awaluddin, Muhammad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study examines the key factors influencing Motor Vehicle Fuel Tax (PBBKB) revenue and its impact on regional expenditure in East Kalimantan Province. The increasing number of motor vehicles and limited public transportation have contributed to rising fuel consumption, making PBBKB a vital component of regional income. However, the interplay between population growth, inflation, regional economic activity (GRDP), and tax revenue remains underexplored in this context. This research aims to evaluate the effects of motor vehicle numbers, population size, inflation rate, and Gross Regional Domestic Product (GRDP) on PBBKB revenue and, subsequently, the effect of PBBKB revenue on regional expenditure. Utilizing a quantitative approach, the study employs the Two-Stage Least Squares (2SLS) method to address potential endogeneity and ensure robust causal inferences. Ten years of time-series data from 2015 to 2024 were analyzed using SPSS version 27. The findings reveal that the number of motor vehicles, inflation, and GRDP have significant positive effects on PBBKB revenue, while population size does not significantly influence it. Moreover, PBBKB revenue has a substantial positive impact on regional expenditure. These results suggest that strategic management of fuel consumption and regional economic growth can enhance tax revenue and support sustainable public spending. This research provides practical insights for policymakers to optimize local tax administration and fiscal planning in resource-rich regions like East Kalimantan.